The foundations of an inclusive paradigm for contemporary education - Alekhina, Svetlana V.; Samsonova, Elena V.; Yudina, Tatiana A. (Special Education, 2018)
The aim of the article is a theoretical modeling of the inclusive paradigm of contemporary education. The study was based on a literature study and secondary data analysis. The article presents the data collected in Russia in 2014-2017. Based on an analysis of the inclusive paradigm conceptual framework, the statements of culturalhistorical theory and system-activity methodology as well as the results of empirical studies on inclusive education, the authors come to conclusions on the conditions of an inclusive paradigm development. The evolution of the inclusive paradigm in contemporary education requires the implementation of various models of professional cooperation, as well as new technologies and methods based on the theory of joint activities.
Keywords: inclusion; inclusive education; special educational needs; methodology; cultural-historical theory; individualization of education